Global design history - Adamson, Glenn; Riello, Giorgio; Teasley, Sarah 1973- (London Routledge, 2011)
This book gathers together a number of leading design historians whose research points the way forward, aiming to address and promote changes to design history.
Towards global design history / Sarah Teasley, Giorgio Riello, Glenn Adamson -- The global renaissance: cross-cultural objects in the early modern period / Marta Ajmar-Wollheim, Luca Molà -- Response / Dana Leibsohn -- Global design in Jingdezhen: local production and global connections / Anne Gerritsen -- Response / Beverly Lemire -- Indian cottons and European fashion, 1400-1800 / John Styles -- Response / Prasannan Parthasarathi -- Import substitution, innovation and the tea ceremony in fifteenth- and sixteenth-century Japan / Christine M.E. Guth -- Response / Maxine Berg -- The globalization of the fashion city / Christopher Breward -- Response / Simona Segre Reinach -- Performing white South African identity through international and empire exhibitions / Dipti Bhagat -- Response / Angus Lockyer -- 'From the far corners' : telephones, globalization, and the production of locality in the 1920s / Michael J. Golec -- Response / Anne Balsamo -- The globalization of the Deutscher Werkbund: design reform, industrial policy, and German foreign policy, 1907-1914 / John Maciuika -- Response / Paul Betts -- Where in the world is design? The case of India, 1900-1945 / Victor Margolin -- Response / Christopher Pinney -- Handmade modernity: post-war design in Turkey / Gökhan Karakus -- Response / Edward S. Cooke, Jr. -- Old empire and new global luxury: fashioning global design / Peter McNeil -- Response / Shehnaz Suterwalla -- Analyzing social networking websites: the design of Happy Network in China / Basile Zimmermann -- Response / Ngai-Ling Sum -- From nation-bound histories to global narratives of architecture / Jilly Traganou -- Response: global agoraphobia / Lucia Allais -- e-Artisans: contemporary design for the global market / Tom Barker, Ashley Hall -- Response / Shannon May.
Keywords: Design -- History; Culture and globalization